Stratifikasi Sosial dan Minat Petani Milenial pada Komoditas Sayuran di Kabupaten Bangka Tengah - Saputra, Andika; Kolopaking, Lala M; Sjaf, Sofyan (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
The decreasing interest of young workers in the agricultural sector can threaten agricultural sustainability and food security. This research aims to analyze the social stratification and interest of millennial farmers in vegetable commodities, determine the factors that influence interest. This research uses mixed methods research with a sequential explanatory research type. The research was conducted in the Central Bangka Regency from Septemberi 2023 to February 2024. This research involved 117 respondents and 30 informants. The quantitatif data analysis was performed using Microsoft Excel and SPSS version 25. Qualitative data were analyzed using the Miles and Huberman interactive model. The research results place experience indicators valued by millennial farmers. Millennial farmers' interest in vegetable commodities was in the very high category (88.00%). The results of the multiple linear regression show that commodity variables, digital technology, environment, and government support simultaneously or partially have a significant effect on the interest of millennial farmers, with a simultaneous contribution of 44.60%. Environmental variables are the variables that most strongly influence the interests of millennial farmers.